2022
DOI: 10.3390/ijms23147541
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinerol and NSC-34 Transcriptomic Analysis: Is the Dose Who Makes Neuronal Differentiation?

Abstract: Cannabis sativa L. proved to be a source of several phytocompounds able to help patients facing different diseases. Moreover, these phytocompounds can help ameliorate general conditions and control certain unpleasant effects of diseases. Some cannabinoids, however, provided more benefits applicable to settings other than palliative care. Using the NSC-34 cell line, we evaluated the barely known phytocompound named cannabinerol (CBNR) at different doses, in order to understand its unique characteristics and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Recently, minor cannabinoids, such as ∆ 8 -THC and CBNR, have also been studied to elucidate whether they exhibit similar neuroprotective properties compared to major ones [13,14]. In this regard, ∆ 8 -THC protected retinoic acid-differentiated neuroblastoma SH-SY5Y cells against amyloid beta (Aβ) toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, minor cannabinoids, such as ∆ 8 -THC and CBNR, have also been studied to elucidate whether they exhibit similar neuroprotective properties compared to major ones [13,14]. In this regard, ∆ 8 -THC protected retinoic acid-differentiated neuroblastoma SH-SY5Y cells against amyloid beta (Aβ) toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused our attention on CBNR, a geometric isomer of CBG, that we have previously tested for its involvement in neuronal differentiation [14]. Here, we investigated the impact of CBNR on the physiology of NSC-34 motor-neuron-like cells and its effects on the regulation of synaptic-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the evaluation of CBG as a neuroprotective agent is much less reported. Recently, a preclinical study reported that the CBG pre-treatment of the NSC-34 cellular line before the injury, was able to attenuate apoptosis signaling and was proposed as an effective neuroprotective agent (Valeri et al 2022). Another study has shown that CBG pre-treatment reduces the loss of cell viability induced by the medium of LPS-stimulated macrophages in NSC-34 cells (Gugliandolo et al 2018).…”
Section: Neuroprotective Property Of Cbd and Cbgmentioning
confidence: 99%